The Impact of National Health Insurance on Community Pharmacies: A Case Study of the Western Region of Ghana - Adjei, Moses Amoah (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration, June, 2012